Integrative genomics positions MKRN1 as a novel ribonucleoprotein within the embryonic stem cell gene regulatory network. (11th August 2015) - Cassar, Paul A; Carpenedo, Richard L; Samavarchi‐Tehrani, Payman; Olsen, Jonathan B; Park, Chang Jun; Chang, Wing Y; Chen, Zhaoyi; Choey, Chandarong; Delaney, Sean; Guo, Huishan; Guo, Hongbo; Tanner, R Matthew; et al.
Abstract In embryonic stem cells (ESCs), gene regulatory networks (GRNs) coordinate gene expression to maintain ESC identity; however, the complete repertoire of factors regulating the ESC state is not fully understood. Our previous temporal microarray analysis of ESC commitment identified the E3 ubiquitin ligase protein Makorin‐1 (MKRN1) as a potential novel component of the ESC GRN. Here, using multilayered systems‐level analyses, we compiled a MKRN1‐centered interactome in undifferentiated ESCs at the proteomic and ribonomic level. Proteomic analyses in undifferentiated ESCs revealed that MKRN1 associates with RNA‐binding proteins, and ensuing RIP‐chip analysis determined that MKRN1 associates with mRNAs encoding functionally related proteins including proteins that function during cellular stress. Subsequent biological validation identified MKRN1 as a novel stress granule‐resident protein, although MKRN1 is not required for stress granule formation, or survival of unstressed ESCs. Thus, our unbiased systems‐level analyses support a role for the E3 ligase MKRN1 as a ribonucleoprotein within the ESC GRN.